2006
DOI: 10.1007/s00425-006-0397-7
|View full text |Cite
|
Sign up to set email alerts
|

The Triticum aestivum non-specific lipid transfer protein (TaLtp) gene family: comparative promoter activity of six TaLtp genes in transgenic rice

Abstract: Plant non-specific lipid transfer proteins (nsLTPs) are encoded by a multigene family and support physiological functions, which remain unclear. We adapted an efficient ligation-mediated polymerase chain reaction (LM-PCR) procedure that enabled isolation of 22 novel Triticum aestivum nsLtp (TaLtp) genes encoding types 1 and 2 nsLTPs. A phylogenetic tree clustered the wheat nsLTPs into ten subfamilies comprising 1-7 members. We also studied the activity of four type 1 and two type 2 TaLtp gene promoters in tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 61 publications
1
39
0
Order By: Relevance
“…Similarly, TaLTP6 in group C lost all its functions in response to the tested abiotic stresses. These results support the previous hypothesis asserting that the expression of the TaLTP gene may be correlated with multiple gene functions, particularly for the genes among different groups; however, their true physiological functions remain to be elucidated in greater detail (Boutrot et al 2007;Jang et al 2007Jang et al , 2008. In an effort to assess the expression of TaLTP genes at the tissue and cellular levels, we assessed the promoter activity of seven TaLTP genes using a promoter::uidA fusion strategy in transgenic Arabidopsis.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Similarly, TaLTP6 in group C lost all its functions in response to the tested abiotic stresses. These results support the previous hypothesis asserting that the expression of the TaLTP gene may be correlated with multiple gene functions, particularly for the genes among different groups; however, their true physiological functions remain to be elucidated in greater detail (Boutrot et al 2007;Jang et al 2007Jang et al , 2008. In an effort to assess the expression of TaLTP genes at the tissue and cellular levels, we assessed the promoter activity of seven TaLTP genes using a promoter::uidA fusion strategy in transgenic Arabidopsis.…”
Section: Resultssupporting
confidence: 78%
“…The broad promoter activities described in this study raise certain consistencies as compared with other previously conducted expression analyses of the 9 KDa nsLTP. For instance, the tissuespecific expression patterns noted in young leaves, shoots, flowers, and seeds were noted previously for nsLTP promoters from rice (Guiderdoni et al 2002), tobacco (Sohal et al 1999), wheat (Boutrot et al 2007), barley (Federico et al 2005) and Arabidopsis (Thoma et al 1993). In wheat, using in situ hybridization, the transcripts of TaLTP3 were also reported to be localized in the epidermal and cortical cells of the leaf, as well as the vascular tissue of the phloem (Jang et al 2005).…”
Section: Resultsmentioning
confidence: 81%
“…Also, the expression of TaLTP genes is developmentally regulated in seeds (Boutrot et al, 2005). Different responsive profiles of TaLTP genes were identified in plant organs by detecting promoter activity fused with GUS in transgenic Arabidopsis or Oryza (Boutrot et al, 2007). The variable expression profile of TaLTPs suggested that TaLTPs may be involved in multiple biological processes.…”
Section: Introductionmentioning
confidence: 99%
“…LTPs regulate lipid transport, homeostasis and lipid-mediated cellular processes [66]. Within grain, several LTPs have been observed up-regulated in aleurone cells around the embryo, scutellum and vascular bundle of the embryo, resulting maximum accumulation of lipids in embryo in grains [67], [68]. Their role in providing protection to embryo from pathogen attack has been speculated [65], [67], [68].…”
Section: Resultsmentioning
confidence: 99%